2017
DOI: 10.1016/s0140-6736(17)32290-0
|View full text |Cite
|
Sign up to set email alerts
|

Clinical efficacy and safety of achieving very low LDL-cholesterol concentrations with the PCSK9 inhibitor evolocumab: a prespecified secondary analysis of the FOURIER trial

Abstract: Amgen.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

13
312
3
22

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 555 publications
(350 citation statements)
references
References 30 publications
13
312
3
22
Order By: Relevance
“…Later analysis from the overall FOURIER cohort has shown a strong relationship between lower achieved LDL‐C, including to very‐low LDL‐C levels, and a progressive reduction of cardiovascular events,25 consistent with our observation of a lower rate of MACE in women and men with lower on‐treatment LDL‐C levels (Figure 4A). In line with results from the FOURIER trial8 and the CTT Collaboration,4 in our study, the P for heterogeneity between men and women was not significant for overall effects.…”
Section: Discussionsupporting
confidence: 88%
“…Later analysis from the overall FOURIER cohort has shown a strong relationship between lower achieved LDL‐C, including to very‐low LDL‐C levels, and a progressive reduction of cardiovascular events,25 consistent with our observation of a lower rate of MACE in women and men with lower on‐treatment LDL‐C levels (Figure 4A). In line with results from the FOURIER trial8 and the CTT Collaboration,4 in our study, the P for heterogeneity between men and women was not significant for overall effects.…”
Section: Discussionsupporting
confidence: 88%
“…The magnitude of cardiovascular benefit of evolocumab in FOURIER (with a reduction in LDL‐C from 92 to 30 mg/dL) over 2.2 years63 was close to the range expected based on the Cholesterol Treatment Trialists’ meta‐analysis of statin trials, which reported a 22% relative risk reduction over 5 years per 1 mmol/L (39 mg/dL) LDL‐C reduction 87. Improved cardiovascular outcomes were observed down to LDL‐C levels as low as 8 mg/dL, with no significant associations between such very low LDL‐C levels and AEs 88. Together with the GLAGOV findings, these results show that patients with ASCVD benefit from LDL‐C lowering below current targets 63.…”
Section: Impact Of Pcsk9 Inhibitors On Atherosclerosis and Cardiovascsupporting
confidence: 78%
“…statin with or without ezetimibe) (-27% myocardial infarction, -21% stroke, -22% coronary revascularizations) during a median period of 2.2 years of follow up. Thus, in the FOURIER trial achieved LDL-C concentration were substantially lower than those observed in all of the previous clinical trials with any lipid-lowering therapy [8] including the IMPROVE-It trial [5].…”
mentioning
confidence: 67%
“…In some preliminary analyses, the benefits obtained by the reduction in serum LDL-C levels to 30 mg/dl were claimed to be not linearly correlated to the achieved serum LDL-C concentrations [8]. Thus, the reduction in cardiovascular events seemed lower than expected and thereby suggested the existence of a plateau of the benefits obtainable by lipid lowering strategies.…”
mentioning
confidence: 96%